Analysis of Environmental Impact and Waste Management of Egg Poultry Industry in the Philippines: A Case of San Jose, Batangas - Dili, Ramces M.; Kalaw, Ruthra Mae B.; Miguel, Anne Dominique L.; Ting, Gloria M. (Journal of Sustainability and Environmental Management, 2022)
The poultry industry produces a lot of waste, and environmental issues grow as the egg industry expands. Poultry owners in the Philippines, notably in San Jose, Batangas, face numerous waste management concerns. This study examined these issues as well as their environmental safety policies. San Jose, in Batangas province, is renowned as "The Egg Basket of the Philippines" for its large-scale egg production. This study collected data using qualitative descriptive analysis. The poultry farms in the municipality were about 376 as of 2021, but with no definite total number of poultry owners. Interviews with the municipal agriculturist and ten poultry owners was utilized. The study revealed substantial waste management difficulties such as manure disposal, water and air pollution, odor disturbance and insects, weather conditions, and virus outbreaks (bird flu). The study's concerning SDGs were 6 (Clean Water and Sanitation) and 12 (Responsible Consumption and Production). Waste disposal over the past decades still poses a threat to the environment. The local government adopted poultry ordinances/resolutions: Resolution 164 of 2008, Resolution 341 of 2016, and Resolution 348 of 2016/Ordinance 007 series of 2016. These policies and initiatives were concluded to be environmentally friendly, but most poultry owners lack awareness of the said policies. Awareness is vital for better policy responses, and the municipality needs to develop its information dissemination. It is essential to improve waste management policies and farm monitoring methods. The local government should implement concrete socioeconomic and environmental programs to empower residents and poultry owners, especially the younger generation, and improve the municipality's knowledge of waste management techniques.